THE STRATEGY OF ALLEGORY IN TUESDAYS WITH MORRIE’S NOVEL BY MITCH ALBOM (A STYLISTICS APPROACH) - Satri Asriyanti (JOEL: Journal of Educational and Language Research, 2021)
This research discusses allegory’s strategy and aims to find out how does the author delivers the message in Mitch Albom’s “Tuesdays with Morrie’s through allegory”. This research was conducted in order to give more knowledge about the allegory’s strategy work in the text and make the wisdom more conveyed to the reader. This research focused on analyzing novel using the theory of Allegory by Dante Alighieri. The data were analyzed using the descriptive qualitative method. The main instrument of the research is the author herself. This finding shows that there were totally four stages: Literal meaning, allegorical meaning, moral impression, and anagogic meaning. In this part, all of that terms were displayed. As the result of this study, the author found there are two main points that the author gets. The first is the allegory representing the imagination of the character (Mitch). The second is allegory can deliver morality.